Effects of European funding on the convergence of central and eastern European countries - Banova, Mariyana Pavlova-; Stoyanova, Mariela (International Journal of Innovative Research and Scientific Studies, 2024)
This study aims to analyze the effects of European funding for Central and Eastern European countries (CEE) on the degree of convergence. The model for measuring the real β-convergence and the standard regression equation when working with a general population were mainly used as part of the analysis methodology. The results confirm the tested neoclassical hypothesis that less developed countries record faster growth rates relative to stronger developed countries. The analysis finds that only in Bulgaria of the studied countries is an independent impact of EU financing on real convergence expressed in the inflation rate. When examining the unemployment rate, a relationship is found in three of the CEE countries: Lithuania, Latvia and Bulgaria. Indicators from the analysis of the relationship between EU funding and convergence through the Gini index are found only in Slovenia while the same observed relationship expressed through GDP per capita shows a negligible independent influence on real convergence in all CEE countries. The study in its entirety demonstrates the relationship between the real effects of European funding on the convergence of CEE countries through four independent variables and raises discussion questions about the approaches to measure the real effect of the budgetary resources allocated at the European level.